The genus Ortholaba (Hymenoptera: Ichneumonidae: Diacritinae) with description of a new species - Sun, Shu-Ping; Sheng, Mao-Ling (Zootaxa, 2006)
Two species of the genus Ortholaba are reported. One, Ortholaba laevis collected from Jilin province, China, is new to science. A key to the species of Ortholaba is presented.